2017
DOI: 10.4103/1658-354x.197344
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the efficacy of dexmedetomidine and tramadol on post-spinal anesthesia shivering

Abstract: Background:Shivering is a common postanesthesia adverse event with multiple etiologies. At present tramadol is a widely used drug for the control of shivering. However, tramadol may cause a lot of nausea and vomiting. Hence, the need to find a better drug with less of side effects. The aim of this study was to compare the efficacy of dexmedetomidine and tramadol in the treatment of post-spinal anesthesia (SA) shivering as well as to compare their side-effect profile.Materials and Methods:This prospective, doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 7 publications
0
30
1
Order By: Relevance
“…In our study Tramadol is given in dose of 0.5mg/kg based on previous studies that used tramadol in a dose of 0.5mg/kg Table-5 and was found safe and effective for control of shivering. [12][13][14][15] Ondansetron is given in a dose of 8mg was selected based on the study by Mahoori et. al, 16 in year 2014 where they concluded that ondansetron and Pethidine have similar effects on shivering and that 8 mg of intravenous ondansetron can control shivering and is the dose of choice.…”
Section: Discussionmentioning
confidence: 99%
“…In our study Tramadol is given in dose of 0.5mg/kg based on previous studies that used tramadol in a dose of 0.5mg/kg Table-5 and was found safe and effective for control of shivering. [12][13][14][15] Ondansetron is given in a dose of 8mg was selected based on the study by Mahoori et. al, 16 in year 2014 where they concluded that ondansetron and Pethidine have similar effects on shivering and that 8 mg of intravenous ondansetron can control shivering and is the dose of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Different drugs that act on these receptors have been examined in different trials for the prevention or treatment of shivering after SA(4). The studied drugs include meperidine, fentanyl, clonidine, ketamine, and tramadol; they have resulted in different degrees of efficacy and many associated side effects, such as haemodynamic instability, respiratory depression, nausea and vomiting(27).Dexmedetomidine(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and magnesium sulfate(2,3,(17)(18)(19)(20) have been demonstrated to be effective and safe for the prevention and treatment of shivering following SA; their efficacy and safety are equal or superior to other adjuvants, with fewer adverse effects. Few trials(3,5,15,17) have examined intrathecal administration to prevent SA-related shivering.…”
mentioning
confidence: 99%
“…[ 8 ] Different pharmacological agents studied for their potential in prevention of peri- or post-operative shivering include clonidine, tramadol, dexmedetomidine, ondansetron, granisetron, ketamine, and pethidine. [ 2 3 10 11 12 13 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 18 ] Clonidine, a α 2 receptor agonist is effective in reducing the incidence of shivering and decrease oxygen consumption during recovery from anesthesia Kundra et al . [ 10 ] The anti-shivering effect of clonidine is because of the actions at three levels; hypothalamus, locus coeruleus, and spinal cord. The postulated mechanisms include alteration of thermoregulatory threshold for vasoconstriction, activation of α 2 receptors at the spinal cord level and release of norepinephrine and other mediators.…”
Section: Introductionmentioning
confidence: 99%